High-temperature in-process inspection followed by 96-h robotic inspection of intentionally manufactured hydrogen crack in multi-pass robotic welding. (February 2021) - Javadi, Yashar; Mohseni, Ehsan; MacLeod, Charles N.; Lines, David; Vasilev, Momchil; Mineo, Carmelo; Pierce, Stephen G.; Gachagan, Anthony
Abstract: This investigation introduces two new techniques to quantitatively address the challenging problem of understanding Hydrogen Induced Cracking (HIC) in welding processes. The first technique is a novel procedure to create a known and controlled HIC in a welded sample. The second is an in-process monitoring technique to measure the initial formation and subsequent growth of the HIC in a multi-pass weld whilst being compatible with the high temperatures associated with the welding process. The HIC was initiated using a localised quenching method of the weld and its character was verified using both macrograph and microscopic investigations. During HIC initiation and growth, the sample was monitored every 1–30 min for a total of 96 h using a custom non-destructive testing (NDT) system, mounted on a robot which ensured repeatable inspection positioning. Combining these techniques has therefore allowed for the first time, a detailed understanding of the evolution of HIC in a multi-pass welded sample. Our findings reveal that the HIC was initiated 43 min after the weld ended and that it then grew rapidly for about 15 min and continued growing at a slower rate for around 24 h. No significant growth was observed for the remaining 72 h of the experimental measurement. Graphical abstract: Image 1 Highlights: A novel procedure to create a known and controlled hydrogen crack is introduced. An in-process high-temperature monitoring technique is also used. Above combination allowed HIC measurement without cooling requirements of the weld. HIC was initiated 43 min after the weld ended. HIC grew rapidly for about 15 min and continued growing for 24 h.